2016
DOI: 10.1590/0004-282x20160109
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal eye movements in three types of chorea

Abstract: Chorea is an abnormal movement characterized by a continuous flow of random muscle contractions. This phenomenon has several causes, such as infectious and degenerative processes. Chorea results from basal ganglia dysfunction. As the control of the eye movements is related to the basal ganglia, it is expected, therefore, that is altered in diseases related to chorea. Sydenham’s chorea, Huntington’s disease and neuroacanthocytosis are described in this review as basal ganglia illnesses that can present with abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, other neurodegenerative conditions show impairments in eye movements as well . Abnormalities in ocular motility and saccades are frequent in HD as well . The evaluation of HD patients typically shows increased saccade latency and saccade slowing affecting both the vertical and horizontal planes …”
Section: Discussionmentioning
confidence: 99%
“…However, other neurodegenerative conditions show impairments in eye movements as well . Abnormalities in ocular motility and saccades are frequent in HD as well . The evaluation of HD patients typically shows increased saccade latency and saccade slowing affecting both the vertical and horizontal planes …”
Section: Discussionmentioning
confidence: 99%
“…More recently, two studies have examined the possible effects of HD on the retina using electroretinograms (ERGs). Pearl et al [17] 1 Eye movement dysfunction is beyond the scope of this review and is comprehensively reviewed elsewhere [12,13,14] reported increased ERG amplitudes across a range flash intensities but there no differences in their latency. Conversely, Knapp et al [18] reported reduced ERG amplitudes in single case study of a 25 year old asymptomatic gene carrier with no differences in latencies.…”
Section: The Retinamentioning
confidence: 99%
“…17,18 Chorea is usually generalized but is often asymmetric and may be accompanied by additional manifestations such as obsessivecompulsive and attention deficit disorders, 19 muscle weakness, 20 involuntary vocalizations, 20 and abnormal eye movements. 18,21 The etiology of chorea in SD has long been suspected to be autoimmune. 18 This theory is supported by symptomatic improvement with anti-inflammatory and immune-modulating treatments such as corticosteroids and intravenous immunoglobulin.…”
Section: Infectious/inflammatorymentioning
confidence: 99%
“…17 18 Chorea is usually generalized but is often asymmetric and may be accompanied by additional manifestations such as obsessive-compulsive and attention deficit disorders, 19 muscle weakness, 20 involuntary vocalizations, 20 and abnormal eye movements. 18 21…”
Section: Differential Diagnosismentioning
confidence: 99%